4(m+9)=2(m-5)+2

Simple and best practice solution for 4(m+9)=2(m-5)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(m+9)=2(m-5)+2 equation:


Simplifying
4(m + 9) = 2(m + -5) + 2

Reorder the terms:
4(9 + m) = 2(m + -5) + 2
(9 * 4 + m * 4) = 2(m + -5) + 2
(36 + 4m) = 2(m + -5) + 2

Reorder the terms:
36 + 4m = 2(-5 + m) + 2
36 + 4m = (-5 * 2 + m * 2) + 2
36 + 4m = (-10 + 2m) + 2

Reorder the terms:
36 + 4m = -10 + 2 + 2m

Combine like terms: -10 + 2 = -8
36 + 4m = -8 + 2m

Solving
36 + 4m = -8 + 2m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2m' to each side of the equation.
36 + 4m + -2m = -8 + 2m + -2m

Combine like terms: 4m + -2m = 2m
36 + 2m = -8 + 2m + -2m

Combine like terms: 2m + -2m = 0
36 + 2m = -8 + 0
36 + 2m = -8

Add '-36' to each side of the equation.
36 + -36 + 2m = -8 + -36

Combine like terms: 36 + -36 = 0
0 + 2m = -8 + -36
2m = -8 + -36

Combine like terms: -8 + -36 = -44
2m = -44

Divide each side by '2'.
m = -22

Simplifying
m = -22

See similar equations:

| 6x+5=-x+40 | | w-10=-1 | | 3x+5=(x-9) | | n+9=-14 | | -2h=22 | | 0.60+p=32 | | |x+4|=1 | | 2v^2=16 | | 2x-3=-17.5 | | -4a=-8 | | 0.33+x=22 | | -8-b=11 | | h-9=6 | | 5n+10(n+9)+25(n+30)=1000 | | 2(x+1)+3(x+5)=37 | | 15+0.25=20+0.05 | | 4x-9=6x+7 | | x+-3.2=6.7 | | 8a-6+2a=-2+6a | | 4x=256 | | 5(a+2)+3(2a-1)= | | 6z=24 | | 10x=100000 | | 3y-2*11=(5)6y+5 | | 3-t=1 | | 9x=729 | | 11=2x+17 | | 3y-2*11=6y+5*5 | | 3.7(-87x-3)=3.7(7x-30) | | 8a^2+8+16a= | | 0.16(36-24x)=0.66(9-6x) | | 7b-2+3b=30+6b |

Equations solver categories